Low birth weight profiles at H. Boejasin Hospital, South Borneo, Indonesia in 2010-2012 - Yuni Astria; Christopher S. Suwita; Benedica M. Suwita; Felix F. Widjaja; Rinawati Rohsiswatmo (Indonesian Pediatric Society, 2016)
Background The prevalence of low birth weight (LBW) is still high in Indonesia. Intrauterine growth restriction (IUGR) and prematurity are the most frequent causes. Prematurity has higher mortality rate. Cultural diversity has an impact on regional LBW profiles in Indonesia. However, data on LBW is unavailable in South Borneo.Objective To describe the LBW profiles and in-hospital mortality of newborns at H. Boejasin Hospital, South Borneo.MethodsThis was a cross-sectional study using secondary data from medical records and neonatal registry at H. Boejasin Hospital, Pelaihari, South Borneo from 2010 to 2012. Subjects were newborns with birth weight <2,500 grams. Categorical data was presented in percentages, while survival analysis was assessed by Kaplan-Meier test. The difference among groups was analyzed with log-rank test.Results The proportion of LBW was 20.2% of total live births and the mortality rate was 17.3%. Mortality rates according to birth weight category was 96% in <1000 g group, 62% in 1,000-1,499 g group, 19% in 1,500-1,999 g group, and 4% in 2,000-2,499 g group. The highest hazard ratio was in the <1,000 gram birth weight group (HR 40.21), followed by the 1,000-1,499 gram group (HR 12.95), and the 1,500-1,999 gram group (HR 4.65);(P<0.01). Asphyxia, hyaline membrane disease (HMD), and sepsis were the most common causes of mortality (at 50%, 21%, and 16%, respectively).Conclusion The prevalence of LBW in this study is quite high and mortality of LBW infants is significantly different between each low birth weight category. [Paediatr Indones. 2016;56:155-61.].